Doktrin Kristus (Kristologi) - Gabriel Kurniawan; Lola Enjeliana; Maria Olivia; Sarmauli (CV Edujavare Publishing, 2025)
This paper analyzes Christology as a crucial part of systematic theology, concentrating on the person and activity of Jesus Christ. It examines how Scripture reveals and church history affirms Christ's twofold character as completely human and fully divine. To emphasize Christ's involvement in redemption, key teachings such the Incarnation, Atonement, Resurrection, and Hypostatic Union are covered. The study also highlights the significance of Christological ideas for faith, hope, and moral behavior, as well as their applicability to modern Christian life. This essay emphasizes that a correct understanding of Christ is fundamental to the Christian faith using a theological and biblical perspective.